Contacts to general practice in the 12 months preceding a diagnosis of an abdominal cancer: a national register-based cohort study. (2nd January 2022) - Jessen, Nanna Holt; Jensen, Henry; Falborg, Alina Zalounina; Glerup, Henning; Gronbaek, Henning; Vedsted, Peter
Abstract: Objective: To compare the number of contacts to general practice across 11 types of abdominal cancer in the 12 months preceding a diagnosis. Design: Nationwide register study. Setting: Danish general practice. Subjects: Forty-seven thousand eight hundred and ninety-eight patients diagnosed with oesophageal, gastric, colon, rectal, liver, gall bladder/biliary tract, pancreatic, endometrial, ovarian, kidney or bladder cancer in 2014–2018. Main outcome measures: Monthly contact rates and incidence rate ratios (IRRs) of daytime face-to-face, email and telephone consultations in general practice across different abdominal cancers. The analyses were conducted for each sex and adjusted for age, comorbidity, marital status and education. Results: Compared to women with colon cancer, women with rectal cancer had the lowest number of contacts to general practice (IRR 12 months pre-diagnostic (IRR–12 )=0.86 (95% CI: 0.80–0.92); IRR 1 month pre-diagnostic (IRR–1 )=0.85 (95% CI: 0.81–0.89)), whereas women with liver (IRR–12 =1.23 (95% CI: 1.09–1.38); IRR–1 =1.11 (95% CI: 1.02–1.20)), pancreatic (IRR–12 =1.08 (95% CI: 1.01–1.16); IRR1 =1.52 (95% CI: 1.45–1.58)) and kidney cancer (IRR–12 =1.14 (95% CI: 1.05–1.23); IRR–1 =1.18 (95% CI: 1.12–1.24)) had the highest number of contacts. Men showed similar patterns. From seven months pre-diagnostic, an increase in contacts to general practice was seen in bladder cancer patients, particularly women, compared to colon cancer. Conclusions: Using pre-diagnostic contact rates unveiled that liver, pancreatic, kidney and bladder cancers had a higher and more prolonged use of general practice. This may suggest missed opportunities of diagnosing cancer. Thus, pre-diagnostic contact rates may indicate symptoms and signs for cancer that need further research to ensure early cancer diagnosis. Key points: The majority of cancer patients attend their general practitioner (GP) before diagnosis; however, little is known about the use of general practice across different abdominal cancers. This study suggests that a potential exists to detect some abdominal cancers at an earlier point in time. The contact patterns in general practice seem to be shaped by the degree of diagnostic difficulty. GPs may need additional diagnostic opportunities to identify abdominal cancer in symptomatic patients.